Co-polarized and cross-polarized scattering of an off-axis focused Gaussian beam by a spherical particle. 3. Diffraction, the Debye series, and time-domain scattering. (December 2018) - Laven, Philip; Lock, James A.
Highlights: Calculated polarization-resolved scattering of an off-axis Gaussian beam by a homogeneous spherical particle. Analyzed diffractive scattering in the near-forward direction. Analyzed the behavior of various Debye series terms as a function of scattering angle. Analyzed off-axis Gaussian beam scattering in the time-domain. Abstract: Diffraction in the near-forward direction is examined for the localized model of an off-axis focused Gaussian beam scattered by a sphere when the beam is translated off-axis either in the scattering plane or perpendicular to it. The results are analyzed using the Fraunhofer diffraction approximation. We also obtain various Debye series contributions to the exact GLMT co-polarized VV and HH scattering amplitudes and cross-polarized VH and HV scattering amplitudes, and discuss their interpretation. Time-domain scattering is also considered for both the exact GLMT scattering amplitudes and our approximation to them, for which the sum over azimuthal modes is evaluated analytically. It is found that although the approximation accurately reproduces the overall magnitude of the scattered intensity, it is not as accurate in reproducing the phase of high-frequency oscillations in the intensity.